AI-ASSISTED WRITING TRAINING: TRANSFORMING TEACHERS INTO PRODUCTIVE AUTHORS THROUGH OPTIMIZATION OF ARTIFICIAL INTELLIGENCE TOOLS AT SD N BANJARSARI 5 - Syadeli Hanafi; Mutoharoh Mutoharoh; Dethia Hs Suci Nurani; Ramdan Ramdan; Oktavianto Setyo Nugroho; Phillip G. Queroda (International Journal of Engagement and Empowerment (IJE2), 2026)
Digital transformation in education has increased expectations for teachers’ professional competencies, yet empirical evidence on targeted interventions that enhance primary school teachers’ scholarly writing through AI remains limited. This study aimed to evaluate the effects of an AI-Assisted Writing training program implemented at SD N Banjarsari 5 on teachers’ scientific writing productivity and digital literacy. A descriptive-intervention design with purposive sampling was employed; in-service primary teachers (n recorded) participated in a participatory, hands-on training covering ChatGPT, QuillBot, Grammarly, and Canva. Data were collected via pre- and post-training questionnaires, observation rubrics, structured interviews, and writing artifacts, and were analyzed using paired-sample t-tests for quantitative measures and thematic analysis for qualitative data. The results showed that participants exhibited significant improvements in self-reported writing competence and satisfaction, produced more structured draft manuscripts, and demonstrated enhanced ability to generate ideas, paraphrase academically, and apply digital tools to develop instructional media. Observational and thematic findings also identified persistent gaps in baseline digital skills and ethical awareness regarding AI use. The study contributes empirical evidence that AI-assisted writing interventions can strengthen teachers’ scholarly productivity and digital literacy, and it highlights the need for ongoing capacity-building and clear ethical guidelines to support sustainable implementation in school contexts